The SBRT database initiative of the German Society for Radiation Oncology (DEGRO): patterns of care and outcome analysis of stereotactic body radiotherapy (SBRT) for liver oligometastases in 474 patients with 623 metastases - Andratschke, Nicolaus; Alheid, H.; Allgäuer, Michael; Becker, G.; Blanck, Oliver; Boda-Heggemann, Judit; Brunner, T.; Duma, M.; Gerum, Sabine; Guckenberger, Matthias; Hildebrandt, Guido; Klement, R. J.; et al. (BMC cancer, 2018)
Liver oligometastases; Oligo-recurrence; Oligometastases; Outcome; Stereotactic body radiotherapy; Sync-oligometastases; Treated metastases control